Evaluasi Kesulitan Guru dalam Menerapkan Pembelajaran Sejarah di SDN Pasirgadung 1 Kabupaten Tangerang - Ina Magdalena; Refita Andriani; Yusuf Adhitia Rachman; Khoirunisa Andini Putri; Siti Novita Chandra (RC-INSTITUT, 2020)
Education is a conscious and planned effort to create an atmosphere of learning and learning process for students to actively develop their potential to have spiritual strength, self-control, personality, intelligence, noble character, and the skills needed by themselves and the community. Development can only be done by humans who are prepared through education, to achieve the most perfect human being as a caliph on earth. The development of education or teaching is inseparable and the responsibility of an educator, how the educator is transforming the knowledge possessed by the existing teaching materials, and by paying attention to the method of teaching that is easily accepted by the learners so that the goal is achieved in accordance with what is expected. This research explores history learning integrated with social studies subjects in elementary schools. The method used in this case, Research is an evaluation method that uses responsive evaluation developed by Stake.